Developmental plasticity in reptiles: Insights from temperature‐dependent gene expression in wall lizard embryos. Issue 6 (20th May 2018) - Feiner, Nathalie; Rago, Alfredo; While, Geoffrey M.; Uller, Tobias
Abstract: Many features of the development of reptiles are affected by temperature, but very little is known about how incubation temperature affects gene expression. Here, we provide a detailed case study of gene expression profiles in common wall lizard ( Podarcis muralis ) embryos developing at stressfully low (15°C) versus benign (24°C) temperature. For maximum comparability between the two temperature regimes, we selected a precise developmental stage early in embryogenesis defined by the number of somites. We used a split‐clutch design and lizards from four different populations to evaluate the robustness of temperature‐responsive gene expression profiles. Embryos incubated at stressfully low incubation temperature expressed on average 20% less total RNA than those incubated at benign temperatures, presumably reflecting lower rates of transcription at cool temperature. After normalizing for differences in total amounts of input RNA, we find that approximately 50% of all transcripts show significant expression differences between the two incubation temperatures. Transcripts with the most extreme changes in expression profiles are associated with transcriptional and translational regulation and chromatin remodeling, suggesting possible epigenetic mechanisms underlying acclimation of early embryos to cool temperature. We discuss our findings in light of current advances in the use of transcriptomic data to study how individuals acclimatize and populations adapt to thermal stress. GRAPHICAL ABSTRACT: Temperature has a pervasive effect on embryonic gene expression. Temperature‐dependent expression is enriched for genes associated with epigenetic regulation, pointing towards a mechanistic basis of embryo thermal acclimation. .